Where to focus post-harvest loss efforts? A review of recent evidence, with application to Ghana - Hoffmann, Vivian; Ridolfi, Carlotta; Nwafor, Manson (International Food Policy Research Institute, 2017)
In this note, we summa-rize new evidence from a recent IFPRI study that documents the relative importance of losses in value chains for staple foods in six countries, review the evidence on which crops are most affected by losses, and outline ways to mitigate PHL.